How to Learn Like A Pro - Nissila, Phyllis; Open Textbook Library (Open Textbook Library, 2016)
How to Learn Like a Pro! features the "big six" effective learning/study skills topics: learning styles and preferences, time and materials management, critical thinking and reading, note-taking, memory principles, and test-taking techniques. Each of the six units featuring a total of twenty-three lessons and accompanying exercises (with a dash of humor here and there) were developed with the diverse student body of the community college in mind as well as learners in other educational venues.
Unit 1 Overview--Learning Styles and Preferences; Unit Terms -- Lesson 1.1: The Three Learning Styles -- Lesson 1.2: Visual Learning -- Lesson 1.3: Auditory Learning -- Lesson 1.4: Kinesthetic Learning -- Lesson 1.5: The Brain Dominance Theory -- Lesson 1.6: Howard Gardner's Multiple Intelligences Theory -- To the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 1 -- Unit 2 Overview--Management of Time, Tools, and Study Environment; Unit Terms -- Lesson 2.1: World View and Self Efficacy -- Lesson 2.2: Procrastination -- Lesson 2.3: Schedules and Scheduling -- Lesson 2.4: Graphic Organizers and Study Cards -- Lesson 2.5: Study Areas and Study Groups -- To the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 2 -- Unit 3 Overview--College Level Critical Thinking and Reading; Unit Terms -- Lesson 3.1: Comprehending College Level Reading by Using the Reading Apprenticeship Approach -- Lesson 3.2: Getting the Most Out of Your Textbooks -- Lesson 3.3: Patterns and Context Clues -- Lesson 3.4: Close Reading for LiteratureTo the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 5 -- Lesson 3.5: Math and Science--Tips for Better Comprehension and for Studying -- To the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 3 -- Unit 4 Overview--Listening and Note-Taking; Unit Terms -- Lesson 4.1: Note-Taking Part 1, Listening -- Lesson 4.2: Note-Taking Part 2, Key Information and Formats -- To the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 4 -- Unit 5 Overview--Memory Principles and Techniques; Unit Terms -- Lesson 5.1: Memory Model and Techniques -- Lesson 5.2: Memory as We Age -- To the Instructor: Optional Assignments/Activities/Extra Credit Opportunities for Unit 5 -- Unit 6 Overview--Test-Taking: Pre, Mid, and Post; Unit Terms -- Lesson 6.1: Pre- Mid- and Post-Test-Taking Strategies -- Lesson 6.2: Handling Test Anxiety -- Lesson 6.3: Understanding Test Items
In English.
Description based on print resource
Keywords: Academic achievement -- Textbooks; Education -- Textbooks